PENGARUH TINGKAT PENDIDIKAN FORMAL, PENGALAMAN KERJA, TINGKAT KUALIFIKASI PROFESI DAN COUNTINUING PROFESSION DEVELOPMENT TERHADAP KUALITAS AUDIT DI INSPEKTORAT PROVINSI BENGKULU - Ilham Reza Tuwlah; Dinal Eka Pertiwi; Diah Khairiyah (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This research aims to find out how the level of formal education, work experience, level of professional qualifications and counting professional development affect audit quality at the Bengkulu Province Inspectorate. The problem discussed in this thesis is the quality of audits at the Bengkulu Province Inspectorate. The population of this research is the auditors of the Bengkulu Province Inspectorate which consists of 95 auditors in the Bengkulu Province Inspectorate. The sample used in this research was all of the population, namely 95 Bengkulu Province Inspectorate auditors. The research method used is descriptive qualitative. The data collection method uses a questionnaire using multiple linear regression analysis. The results of this research show that, (1) the level of formal education has an effect on audit quality, (2) work experience has an effect on audit quality, (3) the level of professional qualifications has no effect on audit quality, (4) continuous professional development has an effect on audit quality, ( 5) level of formal education, work experience, level of professional qualifications, and continuous professional development together influence audit quality. Keywords: Formal Education Level, Work Experience, Professional Qualification Level, Continuous Professional Development, Audit Quality